Exploring the relevance of engaging the Orang Asli in Malaysia’s forest management - Diansyah, Mohammad Wahyu; Abas, Azlan; Sakawi, Zaini (Frontiers in Forests and Global Change, 2022)
The positive social and environmental outcomes of involving local and indigenous people in environmental management have made their inclusion in forest management increasingly considered. However, in Malaysia, where indigenous forest-dependent communities, known as the Orang Asli, are not yet involved in forest management, their significance needs to be empirically recorded. This study aims to investigate the relevance of involving the Orang Asli in Malaysia’s forest management. The study employed a participant observational study at Kampung Tanjung Rambai, an Orang Asli settlement located in the Malaysian state of Selangor. Dwelling with the community and engaging in their forest-based lives for a course of 1 month have managed to capture their current relationships with the forest, which were then analyzed to determine their roles as meaningful stakeholders. The results show that the community has maintained a relationship with their land that may ensure the prudent use of resources. Furthermore, their forest-based lives can be regarded as small-scale disturbances in the forest ecosystem, which are necessary for maintaining resilience.